Mohammad Iqbal, al-Ḥaḍarah al-Gharbīyah wa Qaḍayā al-Tajdīd - Salahuddin Al-Nadwi (Studia Islamika, 1995)
Mohammad Iqbal regarded as one of the most important thinkers of India during the turn of the century. He was born in 1873 in Siyalkote, India. Iqbal came from prominent families and religious. Her father is an educated and progressive figure for the size of the community in his day. Rather than send their children to traditional schools, he would prefer a new school Iqbal entered the English language. Towards Iqbal graduated from high school, his father encouraged him to get into a state university in Lahore, where Iqbal completed Bachelor level (BA) in 1897. He specializes in the field of literary Arabic, Persian, and Islamic Studies under the guidance of Shaykh Meer Hassan, a famous intellectual in India.DOI: 10.15408/sdi.v2i1.845